Spectacular malaise: Art and the end of history. Issue 1 (1st July 2019) - Lang, Martin
AbstractThis article makes two main claims: that Debord's concept of the 'integrated spectacle' is related to end of History narratives and that the related concept of 'disinformation' is manifested in new forms of media-driven warfare. These claims are substantiated through a comparative analysis between Debord's texts and contemporary politics, primarily as described by Adam Curtis and by the RETORT collective. The resulting understanding of our contemporary politics is a situation where subjects who appear to be free, are in fact only free to choose between competing brands of neo-liberalism that manipulate and baffle to obfuscate their true agendas. This situation is termed a 'spectacular malaise'. The article then critiques post-Marxist claims to a re-birth of History and therefore a potential end to the spectacular malaise. It argues that the Arab Spring and Occupy movement did not signal an end to the end of History, as they were unable to articulate an alternative vision. This situation is compared to the last days of the Soviet Union, when change also seemed unimaginable. It identifies Mark Fisher's call for activists to demonstrate alternative possibilities and reveal contingency in apparently natural orders to counter the spectacular malaise. Three art collectives are considered as potential candidates to take up this challenge: Women on Waves, Voina and SUPERFLEX. The article concludes that while making actual social and political change is useful for demonstrating alternative possibilities, it is art's symbolic value that reveals contingency and strikes at the heart of the spectacular malaise.